Epidemiological profile of hospitalization for acute myocardial infarction in an emergency care character (Research, Society and Development, 2022)
Acute myocardial infarction is the leading cause of death in the world and significantly compromises the quality of life of individuals. Objective: to determine the epidemiological profile of hospitalizations for AMI, as an emergency care, in the state of Sergipe between 2017 and 2021. Methodology: Epidemiological, cross-sectional, retrospective and descriptive, quantitative study, carried out from the collection of secondary data from the System of Hospital Information (SIH/SUS). The criteria for inclusion in the study were hospitalizations for urgent care in the state of Sergipe, with a time frame between 2017 and 2021. Results: During this period, 5,687 hospitalizations for AMI were reported. Conclusion: The major contribution of this study was to present an epidemiological profile of AMI, in urgency, in the state of Sergipe between the years 2017 and 2021. The number of hospitalizations is increasing, having been affected only in the year 2020 due to the pandemic of COVID-19. Most cases are male, aged between 60 and 69 years and of mixed race. The number of deaths and the mortality rate also decreased in 2020 due to the pandemic, but maintained high averages in relation to other Brazilian states.